Combination of ultrasound-peracetic acid washing and ultrasound-assisted aerosolized ascorbic acid: A novel rinsing-free disinfection method that improves the antibacterial and antioxidant activities in cherry tomato - Jiayi Wang; Zhaoxia Wu; Hongbin Wang (Ultrasonics Sonochemistry, 2022)
Traditional ultrasound (US)-assisted disinfection is only effective during washing. Coating is an effective method to control microbial growth after washing; however, cross-contamination can occur during immersion in the coating aqueous solution. Tap water (TW) rinsing is generally used to remove sanitizer residues after US-assisted washing; however, the Food and Drug Administration stated that rinsing is unnecessary when the peracetic acid (PAA) concentration does not exceed 80 ppm. In this study, we proposed a novel US-assisted hurdle technology of 80 ppm PAA combined with low-frequency US (25 kHz) during washing, followed by US-assisted aerosolization processing (nonimmersion coating). Ascorbic acid (AA), a safe and low-cost agent, was selected as the aerosolization solution. Cherry tomatoes were selected as the model, and the proposed method was compared with traditional US-assisted disinfection methods (US-10 ppm free chlorine washing + TW rinsing and US-5 ppm chlorine dioxide washing + TW rinsing) to analyze the disinfection efficacy and quality changes. During storage, US-PAA + 1%AA facilitated additional 0.7–0.9, 0.6–0.8, 0.7–1.0, and 0.5–1.0 log CFU/g reductions in the counts of Escherichia coli O157:H7, Salmonella Typhimurium, aerobic mesophilic counts, and molds and yeasts, respectively, as compared with traditional US-assisted methods. Sensory properties, color index, total soluble solids, titratable acidity, and weight loss were not negatively affected by any of the treatments. Firmness was slightly reduced after all treatments; however, the firmness of the samples was maintained during storage, in contrast with the decreased firmness observed in the control. Phenolic content and antioxidant activity significantly increased after all treatments. Further analysis of two key enzymes (phenylalanine ammonia-lyase and 4-coumarate-CoA ligase) involved in phenolic synthesis showed that their levels significantly increased following all treatments, leading to an increase in phenolic content and antioxidant activity. This result also indicated that US-assisted washing could act as an abiotic elicitor to increase nutritional content. Overall, US-PAA + 1%AA treatment served as an effective method for disinfecting produce during washing and for controlling microbial growth after washing without prolonging the processing time, which is an advantage over traditional US-assisted washing.